Synthesis of Cu-BTC Metal-Organic Framework for CO2 Capture via Solvent-free Method: Effect of Metal Precursor and Molar Ratio - Pui San Ho; Kok Chung Chong; Soon Onn Lai; Sze Sin Lee; Woei Jye Lau; Shih-Yuan Lu; Boon Seng Ooi (Aerosol and Air Quality Research)
Abstract The Cu-BTC (Copper-1,3,5-benzene tricarboxylate) is one of the representative metal organic frameworks (MOFs) that has shown outstanding performance for carbon dioxide (CO2) adsorption. However, its conventional synthesis duration is relatively long, and the process requires the addition of bulk amounts of organic solvents. Herein, an enhanced solvent-free synthesis strategy was demonstrated in this work for the Cu-BTC synthesis. For this enhanced method, Cu-BTC was synthesized in 3 hours by mechanically grinding the mixture of copper (Cu) metal precursor and BTC organic linker without using solvent. The as-synthesized Cu-BTC samples were analyzed using various characterization techniques to examine and confirm their properties. The thermal stability result revealed that the self-synthesized Cu-BTC could sustain high temperature up to 290°C. Among the samples synthesized at different mole ratios, the Cu-BTC sample with the Cu to BTC mole ratio of 1.5:1 showed the highest BET surface area and the most significant pore volume of 1044 m2 g−1 and 0.62 cm3 g−1, respectively. Its CO2 adsorption capacity was comparable with those fabricated using the solvent-based method, i.e., 1.7 mmol g−1 at 30°C and 1 bar. The results also showed that the synthesized Cu-BTC exhibited regenerative ability up to five adsorption-desorption cycles.